Ancient origin and genetic segregation of canine circovirus infecting arctic foxes (Vulpes lagopus) in Svalbard and red foxes (Vulpes vulpes) in Northern Norway - Urbani, Lorenza; Tryland, Morten; Ehrich, Dorothee; Fuglei, Eva; Battilani, Mara; Balboni, Andrea (Transboundary and Emerging Diseases, 2020)
This is the pre-peer reviewed version of the following article: Urbani, Tryland, Ehrich, Fuglei, Battilani, Balboni. Ancient origin and genetic segregation of canine circovirus infecting arctic foxes (Vulpes lagopus) in Svalbard and red foxes (Vulpes vulpes) in Northern Norway. Transboundary and Emerging Diseases. 2020;00:1-11, which has been published in final form at https://doi.org/10.1111/tbed.13783. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Canine circovirus (CanineCV) is a relatively new viral species, belonging to the family Circoviridae , whose pathogenic role is still uncertain. Since its first description in one domestic dog in 2011 from the USA, several reports have been documenting its distribution worldwide. Recently, CanineCV was also detected in wild animals such as wolves, foxes and badgers. In order to investigate the presence and the genetic characteristics of CanineCV in foxes of Arctic and Sub‐Arctic regions, the presence of CanineCV DNA in internal organs (liver and spleen) of 51 arctic foxes ( Vulpes lagopus ) from Svalbard archipelago and 59 red foxes ( Vulpes vulpes ) from Northern Norway, sampled from 1996 to 2001 and from 2014 to 2018, respectively, was screened by real‐time PCR. CanineCV was detected in 11/51 arctic foxes and in 10/59 red foxes, backdating the circulation of the virus at least to 1996 in the arctic fox population. The complete genome of 14 identified CanineCV was sequenced and analysed showing an identity higher than 80.8% with the reference strains available to date. According to the species demarcation threshold of 80% genome‐wide nucleotide sequence identity for members of the family Circoviridae provided by International Committee on Taxonomy of Viruses (ICTV), all the CanineCV belong to a single species. Phylogenetic analysis revealed that all the CanineCV were subdivided into five main clusters with one including only CanineCV identified in foxes. Furthermore, CanineCV ...